Gas-Forming Liver Abscess versus Emphysematous Hepatitis: A Radiologic Diagnostic Dilemma—A Case Report and Review of the Literature. (16th July 2019) - Ghosn, Youssef; Abdallah, Ali; Hussein Kamareddine, Mohammed; Geahchan, Amine; Baghdadi, Ahmad; El-Rassi, Ziad; Chamseddine, Abbas; Ashou, Raja
Abstract : A 38-year-old diabetic woman, with history of cholecystectomy and ventral hernia repair, was hospitalized due to sudden-onset abdominal pain and fever. Computed tomography revealed a mixed collection containing necrotic debris and emphysematous change in the left lobe of the liver mainly in segments II and III. These radiological findings suggested emphysematous hepatitis (EH). The patient's condition deteriorated rapidly, and she was rushed to the operating room for urgent exploratory laparotomy where debridement was performed. Intraoperatively the patient was found to have an abscess with incomplete capsule concurrent with hepatic necrosis suggesting the co-occurrence of abscess and EH. The patient survived and was discharged after 13 days. Relevant literature was reviewed, and to the best of our knowledge, EH is an extremely rare entity with limited data regarding its pathogenesis, causative organisms, and management. EH is a rapidly invasive disease process that can be fatal if appropriate therapeutic intervention is delayed. Initial presentations are usually subtle, thus high clinical and radiological suspicion is required for early diagnosis and management to decrease associated mortality and morbidity. We hence report the first successfully treated case of EH with review of the literature.